Diasporic Distresses and Female Expression in the poems of Meena Alexander and Sujata Bhatt - Thakur, Sapna; Singh, Sharanpal (The journal of contemporary issues in business and government, 2021)
Present paper deals with Meena Alexander’s River and Bridge and Sujata Bhatt’s Brunizem. It attempts to show how the female poets have discovered their own voices and developed their sensibilities. Alexander and Bhatt both are diasporic poets. Indian Diasporic poetry addresses the issues of alienation, displacement and rootlessness and explores the problems of migration and diasporic life. Diaspora is a huge and vast concept in literature. Indian writers have immensely contributed to the growth of Diasporic poetry in English. Many Indian women poets write about their personal experiences, displaying feminine consciousness. The women poets of Indian diaspora have migrated to and settled in various countries like Denmark, Germany, Australia, England, and USA. Though they have settled abroad, they are connected to Indian soil and differ from Western behavioral patterns. Their poetry reflects the tensions caused by their Indian psyche in the alien situation. They express diasporic distress and female expression through their poetry. Meena Alexander and Sujata Bhatt successfully manage diasporic distress and try to assimilate into the new culture. They discovered that separation from mother tongue meaning loss of identity and feels alienated. Both the female poets talk about universal fear of poets: the fear of leaving “no word… “no following voices”, and the fear of becoming a “nobody” is present in their poems. The purpose of the paper is to highlight the improved status of women in diasporic community. Diasporic women poets cannot compromise like an average woman with any imposed situation. Their poetry makes a transformation from traditionality to modernity. It is an expression of their changing attitude towards society.